Description of bilateral ideals in a class of noncommutative rings. II - Bavula, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For generalized Weyl algebras containing the universal enveloping algebra U_sl (2, К) of the Lie algebra sl (2) over a field with characteristic zero, bilateral ideals are classified. We show that a product of ideals is commutative and any proper ideal can be uniquely decomposed into a product of primary ideals.